Sharia Buying and Selling Agreements in the Shadow of Artificial Intelligence: Contemporary Jurisprudence Review - Majid Erlangga Hasibuan; Muhammad Raihan Ritonga; Nursania Dasopang (Al Urwah : Sharia Economics Journal, 2025)
The rapid integration of artificial intelligence (AI) into Sharia-based economic transactions introduces fundamental challenges to the validity of classical sales contracts, particularly concerning human intention (irādah), mutual consent (tarāḍī), and the prohibition of uncertainty (gharar). As automated systems increasingly mediate decision-making, traditional fiqh assumptions regarding transparency, agency, and contractual ethics are called into question. This study aims to critically examine the implications of AI-driven transactions for Sharia sales contracts and to formulate a normative reconstruction grounded in fiqh mu‘āmalāt. Employing a qualitative normative-analytical and conceptual-critical approach, this study analyzes classical and contemporary Islamic legal thought alongside recent discussions on AI in Sharia economics. The findings reveal that AI operates not merely as a technical tool but as a structural actor that reshapes contractual relations, generating new forms of opacity and asymmetry that may undermine Sharia principles if left unregulated. Consequently, Sharia contracts in AI-mediated transactions require reconstruction through contextual ijtihād that emphasizes algorithmic transparency, human oversight, and the safeguarding of maqāṣid al-sharī‘ah. This study contributes conceptually by advancing a maqāṣid-oriented framework for evaluating and adapting Sharia contracts in the digital economy, thereby extending the discourse of mu‘āmalāt fiqh beyond classical human-centered paradigms toward ethically responsive AI governance.